2016
DOI: 10.1111/mec.13857
|View full text |Cite
|
Sign up to set email alerts
|

Interactions between parental traits, environmental harshness and growth rate in determining telomere length in wild juvenile salmon

Abstract: A larger body size confers many benefits, such as increased reproductive success, ability to evade predators and increased competitive ability and social status. However, individuals rarely maximize their growth rates, suggesting that this carries costs. One such cost could be faster attrition of the telomeres that cap the ends of eukaryotic chromosomes and play an important role in chromosome protection. A relatively short telomere length is indicative of poor biological state, including poorer tissue and org… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

11
79
3

Year Published

2017
2017
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 62 publications
(93 citation statements)
references
References 90 publications
(83 reference statements)
11
79
3
Order By: Relevance
“…Similar effects can be seen in wild sea birds ( Uria lomvia ), in which the best predictor of among‐year variation in telomere length was environmental quality, with longer telomeres in more food‐rich colonies and years . Effects of environmental harshness were also found in wild salmon, with shorter telomeres in fish growing in colder water . Research on humans has targeted ill effects of overindulgence and obesity and shown (with marginal significance) that telomere length is negatively linked to obesity in women and high glucose levels in men, but with a positive relationship to high‐density lipoprotein (HDL, the “good” cholesterol) in men (using qPCR) …”
Section: Telomere Regulation and Dynamics: Telomerase And Other Mechamentioning
confidence: 67%
“…Similar effects can be seen in wild sea birds ( Uria lomvia ), in which the best predictor of among‐year variation in telomere length was environmental quality, with longer telomeres in more food‐rich colonies and years . Effects of environmental harshness were also found in wild salmon, with shorter telomeres in fish growing in colder water . Research on humans has targeted ill effects of overindulgence and obesity and shown (with marginal significance) that telomere length is negatively linked to obesity in women and high glucose levels in men, but with a positive relationship to high‐density lipoprotein (HDL, the “good” cholesterol) in men (using qPCR) …”
Section: Telomere Regulation and Dynamics: Telomerase And Other Mechamentioning
confidence: 67%
“…Several potential explanations exist for the unexpected negative association between day 4 telomere length and survival to fledgling (Figure a). Hatchlings investing more heavily in somatic maintenance could consequently have fewer reserves available to weather short‐term resource shortages as nestlings, leaving them differentially vulnerable to starvation (see McLennan et al, for similar logic). However, that this survival association was no longer apparent when predated broods were excluded from the analysis (Figure b) and remained apparent when nestlings that likely starved were excluded (Figure c) suggests that broods of nestlings with longer telomeres may have been differentially vulnerable to in‐nest predation, rather than starvation.…”
Section: Discussionmentioning
confidence: 99%
“…DNA was extracted from parent, embryo and fry tissue using the DNeasy Blood and Tissue Kit (Qiagen), as described in McLennan et al. (). For the sperm analysis, sperm was diluted 1/200 with sterile PBS solution.…”
Section: Methodsmentioning
confidence: 99%
“…Telomere length was measured in all samples using quantitative PCR, and data were analysed using qbase software for windows (Hellemans, Mortier, De Paepe, Speleman, & Vandesompele, ), both as described in McLennan et al. (). Atlantic salmon chromosomes are not thought to have a significant amount of interstitial telomere sites (Perez, Moran, & Garcia‐Vazquez, ), which could potentially add noise to the qPCR measurement.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation